Equilibrated PtIr/IrOx Atomic Heterojunctions on Ultrafine 1D Nanowires Enable Superior Dual‐Electrocatalysis for Overall Water Splitting. Issue 20 (14th April 2022) - Huang, Hongpu; Fu, Luhong; Kong, Weiqiang; Ma, Hairui; Zhang, Xue; Cai, Junlin; Wang, Shupeng; Xie, Zhaoxiong; Xie, Shuifen
Abstract: Dual‐active‐sites atomically coupled on ultrafine 1D nanowires (NWs) can offer synergic atomic heterojunctions (AHJs) and high atomic‐utilization toward multipurpose and superior catalysis. Here, ≈2‐nm‐thick PtIr/IrO x hybrid NWs are elaborately synthesized with equilibrated Pt/IrO x AHJs as high‐efficiency bifunctional electrocatalysts for overall water splitting. Mechanism studies reveal the atomically coupled Pt–IrO x dual‐sites are favorable for facilitating water dissociation, alleviating the binding of H* on Pt sites and inversely regulating the *OH adsorption and oxidation on bridge Ir–Ir sites. By simply equilibrating the Pt–IrO x ratio, the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) can be substantially accelerated. In particular, Pt‐rich PtIr/IrO x ‐30 NWs attain 11‐fold enhancements for HER compared to Pt/C in 1.0 m KOH, while IrO x ‐rich PtIr/IrO x ‐50 NWs express about five times mass activity referring to Ir/C for OER. Remarkably, the ratio‐optimized PtIr/IrO x NWs electrode couple achieves a durably continuous H2 production under a substantially low cell voltage. Abstract : Ultrafine PtIr/IrO x hybrid nanowires with equilibrated Pt/IrO x atomic heterojunctions are elaborately synthesized to serve as high‐performance dual‐function electrocatalysts for overall water splitting in alkaline conditions. Atomically coupled Pt–IrO x dual‐sites can mutually arouse electronic‐modulation for substantially accelerating the hydrogen evolution reaction and oxygen evolution reaction, respectively.